Status of operation of the civil and electrical engineering programs of selected higher education institutions in Metro Manila : an assessment - Malitao, William O.; Pelaez, Teodulfo P. (Manila : National University, 1997)
The result of this study will provide empirical data on the status of operation of civil and electrical engineering programs of which may be used as additional bases for the formulation of engineering education development plan which will pave a way for quality and relevant engineering education.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Table of contents -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology and Research Design -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices.
Research Method : Descriptive Method.
Includes bibliographical references.